Smallholder Farmer's Adaptability to Anthropogenic and Climate-Induced Variability in the Dhidhessa River Sub-basin, Ethiopia - Teweldebrihan, Meseret Dawit; Lyu, Haoyang; Pande, Saket; McClain, Michael E. (Frontiers in Water, 2021)
Ethiopia depends on rain-fed agriculture with limited use of irrigation for agricultural production. More than 90% of the food supply in the country comes from low productivity rain-fed smallholder agriculture. Since the livelihoods of many farmers depend on rainfed agriculture, this paper investigates how smallholders adapt to climate variability. Dhidhessa sub-basin of the Blue Nile river basin is home to many vulnerable immigrant smallholders from other parts of Ethiopia. Our study focuses on this sub-basin to understand how crop production and patterns have depended on rainfall. Secondary data on land cover and croplands, the number of households growing crops, crop yields, crop prices and area covered by three major crops (teff, maize and sorghum) are analyzed over a period 2000-2019 and interpreted in light of a primary household survey of 135 farmers in the basin. Results show that almost 40% of the basin is under crop cultivation, and the area under cultivation has been growing 8.6‰ per year. Irrespective of rainfall variability, the number of households practicing crop cultivation has also been growing over the years. This means that more farmers are moving into the basin to cultivate. Analysis reveals that adaptation strategies are at play. Farmer decisions to grow which crops are sensitive to rainfall and their expectations of crop prices resulting from rainfall variability. Their decisions and crop prices are endogenous to the smallholder sociohydrology of the basin, leading more farmers to grow Teff relative to other crops in years of lower rainfall. These decisions are due to the lower sensitivity of Teff prices to rainfall variability and farmers' expectations of higher Teff prices relative to other crops as rainfall decreases. Such behavior also induces climate resilience, enabling farmers not to respond to climate variability rather than migrating out of the basin. Moreover, it allows more farmers to migrate in and engage in crop cultivation within the basin. Such an adaptive strategy based on past experiences offers a way forward to incorporating adaptation mechanisms in sociohydrological models to simulate and assess water futures for similar basins worldwide.